Early outcome of a 31‐gene expression profile test in 86 AJCC stage IB‐II melanoma patients. A prospective multicentre cohort study. (28th February 2019) - Podlipnik, S.; Carrera, C.; Boada, A.; Richarz, N.A.; López‐Estebaranz, J.L.; Pinedo‐Moraleda, F.; Elosua‐González, M.; Martín‐González, M.M.; Carrillo‐Gijón, R.; Redondo, P.; Moreno, E.; Malvehy, J.; et al.
Abstract: Background: The clinical and pathological features of primary melanoma are not sufficiently sensitive to accurately predict which patients are at a greater risk of relapse. Recently, a 31‐gene expression profile (DecisionDx‐Melanoma) test has shown promising results. Objectives: To evaluate the early prognostic performance of a genetic signature in a multicentre prospectively evaluated cohort. Methods: Inclusion of patients with AJCC stages IB and II conducted between April 2015 and December 2016. All patients were followed up prospectively to assess their risk of relapse. Prognostic performance of this test was evaluated individually and later combined with the AJCC staging system. Prognostic accuracy of disease‐free survival was determined using Kaplan–Meier curves and Cox regression analysis. Results of the gene expression profile test were designated as Class 1 (low risk) and Class 2 (high risk). Results: Median follow‐up time was 26 months (IQR 22–30). The gene expression profile test was performed with 86 patients; seven had developed metastasis (8.1%) and all of them were in the Class 2 group, representing 21.2% of this group. Gene expression profile was an independent prognostic factor for relapse as indicated by multivariate Cox regression analysis, adjusted for AJCC stages and age. Conclusions: This prospective multicentre cohort study, performed in a Spanish Caucasian cohort, shows that this 31‐gene expression profile test could correctly identify patients at early AJCC stages who are at greater risk of relapse. We believe that gene expression profile in combination with the AJCC staging system could well improve the detection of patients who need intensive surveillance and optimize follow‐up strategies.